2020
DOI: 10.1021/acs.molpharmaceut.9b01215
|View full text |Cite
|
Sign up to set email alerts
|

Nose-to-Brain Delivery of Cancer-Targeting Paclitaxel-Loaded Nanoparticles Potentiates Antitumor Effects in Malignant Glioblastoma

Abstract: Glioblastoma multiforme (GBM) is an aggressive tumor with no curative treatment. The tumor recurrence after resection often requires chemotherapy or radiation to delay the infiltration of tumor remnants. Intracerebral chemotherapies are preferentially being used to prevent tumor regrowth, but treatments remain unsuccessful because of the poor drug distribution in the brain. In this study, we investigated the therapeutic efficacy of cancer-targeting arginyl-glycyl-aspartic tripeptide (RGD) conjugated paclitaxel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 74 publications
0
25
0
Order By: Relevance
“…44 A number of studies demonstrated that the RGD modied nano-drug delivery systems could improve the active targeting efficiency of tumor cells. [45][46][47][48] Thereby, the ultrasound irritation could mediate the drug-loaded NBs to be more easily internalized into the cells, and the prepared RGD-modied NBs could further improve cellular uptake and increase the delivery efficiency of FTY720. The cellular uptake efficiency of the FTY720@SPION/PFP/NB or FTY720@SPION/PFP/RGD-NB was also evaluated by observing MRI T2-weighted imaging (T2WI) and by measuring T 2 value of HepG2 cells when incubated with different nanoparticles using a clinical 1.5T MRI scanner.…”
Section: Resultsmentioning
confidence: 99%
“…44 A number of studies demonstrated that the RGD modied nano-drug delivery systems could improve the active targeting efficiency of tumor cells. [45][46][47][48] Thereby, the ultrasound irritation could mediate the drug-loaded NBs to be more easily internalized into the cells, and the prepared RGD-modied NBs could further improve cellular uptake and increase the delivery efficiency of FTY720. The cellular uptake efficiency of the FTY720@SPION/PFP/NB or FTY720@SPION/PFP/RGD-NB was also evaluated by observing MRI T2-weighted imaging (T2WI) and by measuring T 2 value of HepG2 cells when incubated with different nanoparticles using a clinical 1.5T MRI scanner.…”
Section: Resultsmentioning
confidence: 99%
“…• In vivo: PLGA-NP (Sousa et al, 2019;Ye et al, 2019;Caban-Toktas et al, 2020;Chung et al, 2020), RGD-NP (Ullah et al, 2020), oleic acid NP (Wang H. et al, 2020) • In vitro only: PLGA-NP (Luque-Michel et al, 2019;Ferreira et al, 2020;Roberts et al, 2020), ethyl arachidate (TPLN) (Alves et al, 2020), FONP (Daniel et al, 2019), pSiNPs…”
Section: Use Experimental Setting and Nanoparticle Typementioning
confidence: 99%
“…2019; Shi et al, 2019;Sousa et al, 2019;Ye et al, 2019;Zhang et al, 2019;Zhao et al, 2019;ZhuGe et al, 2019;Alves et al, 2020;Caban-Toktas et al, 2020;Chung et al, 2020;Ferreira et al, 2020;Kazmi et al, 2020;Liang et al, 2020;Martinez-Rovira et al, 2020;Meng et al, 2020;Roberts et al, 2020;Ullah et al, 2020;Wang H. et al, 2020;Wang X. et al, 2020;Xu et al, 2020;Zhu et al, 2020; see Table 3 for examples of ligand targeting in glioma research). Another active targeting method to increase functional specificity of NPs that are used as gene delivery systems is the transcriptional targeting, which can occur at a transcriptional or posttranscriptional level (Golombek et al, 2018).…”
Section: Radiotherapy Enhancermentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, attention has specifically focused on peptides capable of targeting two of the most overexpressed heterodimers in cancer, i.e. α v β 3 for glioblastoma or ovarian cancers 11 , 17 , 20 , and α 5 β 1 for ovarian and lung cancers 17 , 21 , providing the means for the potential targeted delivery of classical chemotherapeutic agents 22 25 , nucleic acids 26 , 27 , proteins 28 , imaging agents 29 , 30 , or a combination of these 28 , 31 , 32 to malignant cells.…”
Section: Introductionmentioning
confidence: 99%